Employment and Human Resource Development of Disabled People in Japan and Finland: A Comparative Study from the Perspective of Diversity, Inclusion, and Decent Work - Futagami Shiho; Kettunen Erja (Springer, 2022)
By analyzing the best practices in Japan and Finland, this study addresses the measures taken in those countries for enhancing the inclusion of disabled people in working life. The study reviews the existing research on diversity, inclusion, and decent work as well as the support programs for people with disabilities, and compares Japan and Finland in supporting the employment and human resource development (HRD) of disabled people from the perspective of diversity, inclusion, and decent work. The study considers the cases of the Accessibility Consortium of Enterprises (ACE) from Japan and the “Leap to Labour!” and “ILONA” projects of social firms from Finland in supporting the employment and HRD of disabled people. The conclusion section of the study highlights both the future challenges and opportunities in this area and provides a list of the policy implications.
Sustainable Development in Asia : Socio-economic, Financial, and Economic Perspectives